Population Density and Habitat Preferences of the Rinjani Scops Owl (Otus jolandae) in the Mandalika Special Economic Zone, Lombok, Indonesia: Population density and habitat preference of Otus jolandae - Permatasari, Baiq Dewi; Suana, I Wayan; Hadiprayitno, Gito; Tresnani, Galuh (Journal of Tropical Life Science, 2025)
The Rinjani Scops Owl (Otus jolandae) is an endemic species of Lombok, closely associated with Mount Rinjani National Park. In 2023, its range was newly recorded in the Mandalika Special Economic Zone (SEZ), extending its known distribution. Understanding the population density and habitat preferences of this bird is crucial for effective management and conservation. From April to June 2024, a study was conducted in Mandalika SEZ, covering an area of 1,175 hectares. The point count method was used to record individuals based on sightings and calls. Vegetation analysis was performed at observation sites to identify preferred tree species and calculate habitat preferences using the selection index. Twenty-three individuals of O. jolandae were observed across seven sites, with a population density of 0.02 individuals per hectare—lower than densities recorded in Mount Rinjani National Park—which reflects the significant ecological pressures from development activities. The habitat includes 21 tree species, but the owl actively uses only 14 for activities such as perching, roosting, and nesting. Samanea saman had the highest preference index (3.424), making it the most favored tree, followed by Gmelina arborea and Nauclea orientalis. The species relies heavily on large-diameter trees and the middle canopy layer, reflecting its need for stable and protective habitats. This study provides essential data for future conservation programs and highlights the Mandalika SEZ’s potential as a birdwatching ecotourism destination featuring this unique endemic species